A Glycotherapeutic Approach to Functionalize Biomaterials‐Based Systems. (18th March 2020) - Gadekar, Anuja; Bhowmick, Sirsendu; Pandit, Abhay
Abstract: In addition to being one of the primary building block materials of living cells, glycans are also favorable candidates for therapeutic applications. In the mid‐20th century, the progress of glycans in the drug discovery field became surpassed by protein and DNA‐focused treatments. However, the emergence of new analytical tools and methods to synthesize structurally specific glycans has encouraged and motivated the scientific community toward the development of glycan‐based therapeutics. This review discusses the reemergence of glycan‐based agents in the last decade and the technical strategies that played a key role in bringing the glycan‐based treatments into the limelight of modern medicine. The review also includes the application of native glycans as the therapeutic agents along with the chemically engineered cell surface glycans and proteins to meet the preclinical and clinical scenario. Glycan‐based therapeutic materials hold a huge potential that can be harnessed to meet the clinical needs in medicine. Abstract : Glycans are emerging as materials with high therapeutic potential. The review highlights the emergence of glycans from the mid‐20th century to the present along with a brief overview of glycan‐lectin interactions and glycoconjugation strategies for the design of glycan‐functionalized materials, followed by a summary of glycoconjugated biomaterials developed in recent years as drug candidates or targeted delivery systems.